Mengukur Output Gap Ekonomi Maluku Utara (Pendekatan Hodrick-Prescott Filter) - Jufri Jacob; Zulkifly Waibot (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
Development anywhere will always be faced with fluctuating conditions or the ups and downs of economic growth. In the discourse "New Neo-Classical Synthesis" which by (Hubbard, 2014; Gordon, 2014; Mitchell, 2019 and Insukindro, 2020), sees economic fluctuations that can lead to recession and expansion. How to measure the output gap or economic fluctuation that occurred in North Maluku Province and its relationship with economic indicators. Estimation of economic fluctuations uses the Hodrick-Prescott Filter method, which is an econometric method to describe the frequency of time series data becoming trends in an economic cycle. The results showed that North Maluku's economic fluctuations were actually dominated by economic recessions rather than expansion. In the first quarter of 2020, if you use the standard macroeconomic approach, there will still be economic expansion fluctuations (3.06), but the New Neo-Classical Synthesis method since the first quarter has experienced an economic recession (-1.42). Meanwhile, the movement patterns are unidirectional or procyclic, there are also opposites or contersiclic.